Visualizing Biological Membrane Organization and Dynamics - Baaden, Marc (Journal of molecular biology, 2019)
Biological membranes are fascinating. Santiago Ramón y Cajal, who received the Nobel prize in 1906 together with Camillo Golgi for their work on the nervous system, wrote “[…]in the study of this membrane[…] I felt more profoundly than in any other subject of study the shuddering sensation of the unfathomable mystery of life”††The full quotation is “I must not conceal the fact that in the study of this membrane I for the first time felt my faith in Darwinism (hypothesis of natural selection) weakened, being amazed and confounded by the supreme constructive ingenuity revealed not only in the retina and in the dioptric apparatus of the vertebrates but even in the meanest insect eye. There, in fine, I felt more profoundly than in any other subject of study the shuddering sensation of the unfathomable mystery of life.” from the autobiography Recollections of My Life.. The visualization and conceptualization of these biological objects have profoundly shaped many aspects of modern biology, drawing inspiration from experiments, computer simulations, and the imagination of scientists and artists. The aim of this review is to provide a fresh look on current ideas of biological membrane organization and dynamics by discussing selected examples across fields. [Display omitted] •Visualization of biological membranes has determined key aspects of modern biology.•Experimental, computational, and illustrative approaches shape our understanding.•Membrane dynamics spans multiple timescales and length scales.•Complexities in composition in scales and in diversity are a major challenge.•Describing membrane energetics and energy flow may be the next step.